Invasive squamous cell carcinoma: comparison of differentiation grade and tumour depth by anatomical site in 1666 tumours. (1st January 2018) - Pyne, J. H.; Barr, E.; Myint, E.; Clark, S. P.; David, M.; Na, R.
Summary: Background: Invasive squamous cell carcinomas (SCCs) presents with different grades of differentiation and depths of invasion. Aim: To compare the grade of differentiation, tumour diameter and tumour depth by anatomical site in invasive SCC. Methods: Retrospective clinical and histopathological data on consecutive cases of SCC came from a clinic in Sydney, Australia were assessed. A multinomial logistic regression model was applied to compare grades of differentiation by age, sex, anatomical sites, and histological tumour maximum diameter and depth. Results: In total, 1666 SCCs were identified, including 82.1% ( n = 1367) well‐differentiated, 13.3% ( n = 222), moderately differentiated and 4.6% ( n = 77) poorly differentiated SCCs. Patients with poorly differentiated tumours were more likely to be older and male (both P < 0.001). The most common site for poor differentiation was the scalp in men ( n = 12; 15.6%) and the cheek or chin in women ( n = 7; 9.1%). In the multivariate model, compared with well‐differentiated SCC, older age was significantly associated with poorly and moderately differentiated SCC ( P < 0.01 and P = 0.02, respectively). Larger tumour diameters were related to poor differentiation ( P = 0.03). Ear, forehead and chest sites had increased tumour depth and poor differentiation. Conclusions: This study found increased rates of poorly differentiated SCC on the forehead and cheek for both sexes, while men displayed increased rates of poorly differentiated SCC on the bald scalp and the ears. Tumour diameter and depth increased as tumours varied from well‐differentiated to moderately differentiated and from moderately differentiated to poorly differentiated. An increase in depth and increased prevalence of poorly differentiated tumours were found on the ears for men and on various facial sites for both sexes.